PENGABDIAN KEPADA MASYARAKAT PELATIHAN PROGRAMMABLE LOGIC CONTROLLER MENGGUNAKAN OUTSEAL PLC - Direstu Amalia; Setiyo Setiyo; Wahyudi Saputra; Muhammad Indra Martadinata; Virma Septiani; Rio Rizko (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2021)
A programmable Logic Controller or commonly called PLC is a device that is programmed according to the needs of specific industrial processes desired based on logic (arithmetic calculations in an order), which aims to control and regulate the desired process to produce the desired output as well. This community service activity is intended as an implementation of the field of airport engineering technology which is expected to provide increased skills that can be a provision in the world of work for the trainees. The activity was focused on conducting Programmable Logic Controller (PLC) training for high school students in the city of Palembang. The concept of training is carried out for 1 (one) day using an approach of 30% theory and 70% practice. includes the introduction of PLC systems and programming using ladder diagrams which are expected that students who have attended this training will have skills in the field of automation that can be a provision in entering the world of work. The results of the evaluation showed that the average grade in the practicum was 90.5 (ninety points five).